Selecting international judges principle, process, and politics - Mackenzie, Ruth. (Oxford : Oxford University Press, 2010)
International courts are called upon to decide upon a wide range of issues of global importance, yet public knowledge of international judges and the process by which they are appointed remains very limited. Drawing on empirical research, this book explains how the judges who sit on international courts are selected.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International courts; Judges -- Selection and appointment